Effects of Maternal Voluntary Wheel Running During Pregnancy on Adult Hippocampal Neurogenesis, Temporal Order Memory, and Depression-Like Behavior in Adult Female and Male Offspring - Yau, Suk-Yu; Lee, Thomas Ho-Yin; Formolo, Douglas Affonso; Lee, Wing-Lun; Li, Leo Chun-Kit; Siu, Parco M.; Chan, Chetwyn C. H. (Frontiers in Neuroscience, 2019)
Research suggests that maternal exercise in pregnancy may have beneficial effects on the brain function of offspring. This study sought to determine if voluntary wheel running during pregnancy improves depression-like behavior, temporal order memory, and hippocampal neurogenesis in both female and male offspring mice. Pregnant mice were allowed to run voluntarily by introducing running wheels into the housing cages throughout the gestational period. Male and female mice offspring at the age of 8- to 9-week-old offspring were then tested for temporal order test and forced swim test, then euthanized for immunostaining for examining adult hippocampal neurogenesis. Results showed that both male and female pups have reduced depression-like behavior, while only male offspring demonstrated improvement in temporal order memory. Immunostaining revealed that male offspring showed an increase in number of immature neurons in the ventral hippocampus, whereas female offspring show enhanced cell proliferation in the dorsal hippocampus. The findings confirm that maternal physical exercise benefits both female and male offspring on reducing depression-like behaviour, but with gender effect on promoting hippocampal cell proliferation and newborn neurons.